Better vertebrae remodeling in pediatric spinal eosinophilic granuloma patients treated with kyphoplasty and short-term posterior instrumentation: A minimal two-year follow-up with historical controls - Zheng, Yiming; Zhang, Zhiqiang; Wang, Dahui (Frontiers in Pediatrics, 2022)
Objective: To assess the validity and safety of kyphoplasty combined with short-term posterior instrumentation to treat children with vertebrae plana due to eosinophilic granuloma (EG). Patients and Methods: Clinical data of EG patients, who received kyphoplasty and short-term instrumentation from March 2019 to March 2020, were retrospectively reviewed. The recovery of diseased vertebrae was assessed and compared with historical cases’ data. Results: Nine patients with EG had received kyphoplasty and short-term posterior instrumentation. The mean age at initial treatment was 66.7 months old (range, 28-132 months). The mean follow-up time was 26.7 months (range, 24-30 months). Four and 5 cases presented with thoracic and lumbar vertebral destruction, respectively. Under Garg’s classification, 7 and 2 cases were classified as Grade IIA and IIB, respectively. The median diseased vertebral heights at 1-year and 2-year after surgery were significantly higher than the preoperative height. The average percentages of vertebral height to references at 1-year and 2-year after surgery were 72.0% and 86.0%, respectively. The average percentage of vertebral height to references at 2-year after surgery was significantly higher than the historical cases’ average percentage at the same time. No minor or major adverse events were observed. Conclusions: Transpedicular balloon kyphoplasty for the direct restoration of vertebrae plana seems feasible and safe in combination with short-term posterior instrumentation. Better short-time vertebrae remodeling was observed 2 years after surgery. In children with vertebrae plana due to EG, active surgical treatment is advised to retain the ability to restore vertebral height.